Good governance and organization performance in public sector: A proposed framework - Mohd Kamal, Mohd Khirul Azwan; Romle, Abd Rahim; Yusof, Muhammad Suhaimi (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
The matter of governance has become an essential and a critical issue for the public sector particularly in Malaysia.Most of government leaders have stressed and given more focus on the issues of governance, which called for the public sector to work in a system of check and balance.Further, the public service servant, including professional management group and support group recommended to emulate a value system that stress more on the subject of ethics, openness, accountability, transparency, and wholeness in the public sector.This issue needs to be addressed accordingly as it gives bearing on the operation of an establishment.This paper performs to propose a study of good governance on the performance of the organization in the Malaysian public sector.